VP176 Effectiveness Of Anti-Tumor Necrosis Factor In Patients With Psoriatic Arthritis. (12th January 2018) - da Silva, Michael; dos Santos, Jéssica; Almeida, Alessandra; Alvares, Juliana; Guerra, Augusto; Oliveira, Haliton; Rodrigues, Flávia; Bennie, Marion; Godman, Brian; Acurcio, Francisco
Abstract : INTRODUCTION: Anti-tumor necrosis factor drugs (anti-TNF) are the last line of treatment for psoriatic arthritis (PsA) in the guideline of Brazilian Public Health System (SUS). Data of effectiveness of these drugs are scarce in the Latin American population. This study evaluated the effectiveness of the anti-TNF on a cohort of patients with PA in the SUS. METHODS: PsA patients treated with anti-TNF, were included in an open prospective cohort study. The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Clinical Disease Activity Index (CDAI) were used to assess the effectiveness at six months of follow-up. The anti-TNF was considered effective when the patient achieves scores of four or less measured for BASDAI or scores of ten or less for CDAI. Frequency distributions were compiled for the sociodemographic variables and mean and standard deviation (SD) was used for clinical variables. The paired Student t-test was established to evaluate the differences between baseline and 6 months evaluated for BASDAI and CDAI. RESULTS: Fifty-four patients with PsA completed six months of follow-up. The mean age of patients was 54.03 years (10.44) and the mean disease duration was 8.00 years (7.49). Furthermore, 50 percent of the patients were female, 61.1 percent white and 59.6 percent married. The most used anti-TNF was adalimumab (63.0 percent), followed by etanercept (20.4 percent) and infliximab (16.7 percent). The anti-TNF reduced disease activity measured by BASDAI and CDAI at six months of follow-up (p<.001). The percentage of patients achieving the effectiveness with anti-TNF was 61.1 percent measured by BASDAI and 53.7 percent by CDAI. CONCLUSIONS: Anti-TNF drugs demonstrated to be effective in more than half of patients at six months. This result highlighted the importance of the treatment with the anti-TNF drugs in the Brazilian population. Long-term data are needed to confirm these results.